Creative Cities and (Un)Sustainability: From Creative Class to Sustainable Creative Cities - Kagan, Sacha; Hahn, Julia (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2011)
The city today is increasingly conceptualized using terms such as creative cities or creative class and stressing the importance of culture. The effects this development can have on cities and neighbourhoods has been criticised within the wider field of sociology. We explore this critique and place it in the context of the analysis of a culture of unsustainability in order to identify how the concept of creative cities may breed unsustainability. The two cities of Hamburg and Toronto are looked at, considering their implementation of the ideas behind the creative city concept as well as the critical responses from the cultural sector. We then introduce a re-conceptualization of creative cities based on an understanding of the role of the artist in cultures of sustainability. Rethinking creativity and pointing at open dialogue and Richard Sennett's notion of the craftsman, we suggest one possible way toward sustainable creative cities.